2015
DOI: 10.5713/ajas.14.0927
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Intramuscular Fat Percentage in Live Swine Using Real-time Ultrasound to Determine Pork Quality

Abstract: In the modern pork industry, selection of high intramuscular fat (IMF) in pigs is necessary to improve pork quality. Ultrasound has been used previously to predict subcutaneous fat thickness and IMF in the longissimus muscles of line pigs and Real-time ultrasound has also been reported as a reliable method for estimating IMF in live pigs. So we estimate the correlation between meat quality traits and IMF percentage to investigate the possibility of utilizing real-time ultrasound technology for predicting IMF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…This finding agrees well with that of Brewer et al [5] and Cannata et al [29], who showed an increase in the fat content with increased marbling degree. When compared to our results, Jung et al [30] reported lower fat content (2.1% to 2.7%) for the LD muscle of pure breeds (Duroc, Landrace, and Large White) but Muhlisin et al [18] reported higher fat level (5.6% to 6.0%) for the LD muscle of Korean native black pigs. These contrasting results could be attributed to the different pig breeds used among the studies.…”
Section: Resultscontrasting
confidence: 56%
“…This finding agrees well with that of Brewer et al [5] and Cannata et al [29], who showed an increase in the fat content with increased marbling degree. When compared to our results, Jung et al [30] reported lower fat content (2.1% to 2.7%) for the LD muscle of pure breeds (Duroc, Landrace, and Large White) but Muhlisin et al [18] reported higher fat level (5.6% to 6.0%) for the LD muscle of Korean native black pigs. These contrasting results could be attributed to the different pig breeds used among the studies.…”
Section: Resultscontrasting
confidence: 56%
“…With the continuous development of color image processing technology, the reliability of using ultrasound images to predict IMF [ultrasonic methods to predict IMF (UIMF)] has become increasingly high (Newcom et al, 2002; Schwab et al, 2009). Jung et al (2015) found that the genetic and phenotypic correlations for CIMF and UIMF were 0.75 and 0.76, respectively. Due to the low cost, convenience, high accuracy, and non-invasiveness of this technology (Cross and Belk, 1994; Yang et al, 2006; Jung et al, 2015), UIMF has been increasingly adopted in large-scale measurement of IMF.…”
Section: Introductionmentioning
confidence: 97%
“…Jung et al (2015) found that the genetic and phenotypic correlations for CIMF and UIMF were 0.75 and 0.76, respectively. Due to the low cost, convenience, high accuracy, and non-invasiveness of this technology (Cross and Belk, 1994; Yang et al, 2006; Jung et al, 2015), UIMF has been increasingly adopted in large-scale measurement of IMF.…”
Section: Introductionmentioning
confidence: 97%
“…High levels of total fat intake have been shown to increase obesity and cancer risk in industrialized countries (Van Barneveld, 2003). Regarding this, modern pork industry focused their efforts on producing pigs with a lower percentage of fat (Jung et al, 2015) to satisfy consumers' preferences (Van Barneveld, 2003). However, leaner meat results not only in reduction of subcutaneous fat, but also of IMF.…”
Section: Introductionmentioning
confidence: 99%